Analysis of porfolio selection techniques. - Tan, Yvonne Yi Woen. (2008)
Contrary to earlier studies on the performance of value versus growth stocks, the traditional P/E and P/BV ranking strategy carried out in this study found that value stocks do not significantly outperform growth stocks for the period 1994 through 1998. The regression strategy was also examined and the mixed results obtained showed that the regression method was not useful in identifying stocks that would consistently outperform the market.